Wrongoings and disclosure: whistleblowing protection - Ali Mohamed, Ashgar Ali (2018)
This paper discusses on the various types of wrongdoings and the requirement of disclosure. In this regards, the reference has been on the need for whistleblower protection with reference to Whistleblower Protection Act